Magnetic properties of periodic nonuniform spin-1/2XX chains in a random Lorentzian transverse field - Derzhko, Oleg (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1999)
Using continued fractions we examine the density of states, transverse magnetization and static transverse linear susceptibility of a few periodic nonuniform spin-1/2 XX chains in a random Lorentzian transverse field.